The Prevalence of Metabolic Acidosis in Patients with Different Stages of Chronic Kidney Disease: Single-Centre Study - Piotr Kuczera; Dorota Ciaston-Mogilska; Barbara Oslizlo; Anna Hycki; Andrzej Wiecek; Marcin Adamczak (Karger Publishers, 2020)
Background: Metabolic acidosis (MA) is one of the most common consequences of CKD. MA is also a risk factor of CKD progression and increased mortality in these patients. Aim: The aim of this retrospective, cross-sectional study was to assess the prevalence of MA in different stages of CKD and renal replacement therapy (RRT) modalities - haemodialysis (HD) and peritoneal dialysis (PD). Additionally, the relationship between the prevalence of MA and aetiology of kidney disease was analysed. Methods: One thousand five patients in different stages of CKD, or modalities of RRT were enrolled into this single-centre cross-sectional study. Forty-one patients were ruled out because of oral bicarbonate supplementation. In the remaining 964 patients (698 CKD stages 1-5, 226 HD, 40 PD), venous blood HCO3− concentration, as well as serum Cr and urea concentrations were assessed. MA was diagnosed when blood HCO3− concentration was below 22 mmol/L. Results: The prevalence of MA increased among all stages of CKD. Patients on HD had lower prevalence of MA in comparison with CKD 5 patients with no RRT (38.5 vs. 56.0%; p = 0.02) In PD patients, the prevalence of MA was significantly lower than in HD patients (2.5 vs. 38.5%; p < 0.001). In the whole study group, there were no significant differences in the prevalence of MA between different aetiologies of CKD (glomerulonephritis 24%, hypertension 23%, diabetes 25%, and tubule-interstitial diseases 24%). Also, when only patients in stages CKD 3-5 were compared, no significant differences in the prevalence of acidosis were found (glomerulonephritis 28%, hypertension 22%, diabetes 24%, and tubule-interstitial 21%). Conclusions: (1) MA is more frequent in patients with more advanced stages of CKD. (2) RRT reduces the prevalence of MA. (3) In PD patients, MA is rare. (4) Aetiology of CKD seems not to have a significant impact on MA prevalence.